ShotBlocker versus vibration device: Which technique reduces pain and increases satisfaction in insulin injection among type 2 diabetes: A randomized controlled trial - Ali Dhahir Abdulyemmah; Haider Mohammed Majeed (Journal of Integrative Nursing, 2025)
Objective: To evaluate the effects of the ShotBlocker and vibration device on pain intensity and patient satisfaction during subcutaneous (SC) insulin injections in hospitalized adults with type 2 diabetes mellitus. Materials and Methods: In this randomized controlled trial, 102 patients with type II diabetes mellitus were randomly assigned into 3 groups: 35 patients in the ShotBlocker group, 36 patients in the vibration group, and 31 patients in the control group. ShotBlocker was applied immediately before and during the injection, while the vibration was applied for 2–3 s before and during injection. The visual analog scale (VAS) was used for measuring pain and satisfaction of the patients, respectively. Results: There were statistically significant differences in pain scores among the study groups (P = 0.000). The vibration group had significantly lower pain scores (P = 0.000). Similarly, the ShotBlocker group demonstrated significantly lower pain scores (P = 0.000) compared to the control group. Regarding satisfaction scores, there were statistically significant differences among the groups (P = 0.000). The vibration group had significantly higher satisfaction scores (P = 0.000). Similarly, the ShotBlocker group showed significantly higher satisfaction scores (P = 0.000) compared to the control group. Conclusions: The ShotBlocker and vibration device are effective, noninvasive methods for reducing pain and enhancing patient satisfaction during SC insulin injections in adults with type 2 diabetes mellitus.